Parametric study of immersion-Sn plating on Cu effect on reaction kinetics and porosity of deposit - Fajardo, Charlene Jovita I. (2009)
Immersion-Sn is a Pb-free final finish that combines the low cost and process simplicity of organic solderability preservative (OSP) and the surface conductivity of electroless nickel immersion gold (ENIG). It deposits a thin, uniform, and planar Sn layer on Cu following an ion-replacement mechanism that consumes the substrate in-reaction. The process is self-limiting, which means that the reaction stops when the Sn film is thick enough to hinder the reaction. This research aims to determine the deposition kinetics of immersion Sn and to identify the main and interaction effects of plating time, temperature and bath agitation to both thickness and porosity of deposit.
Electrolytic tough pitch (ETP) Cu coupons were immersion-plated at temperatures 49, 63, and 77 degree celcius for 1, 3 and 5 minute increments from 5-90 minutes. Thicknesses were measured using a scanning electron microscope (SEM), results of which show that considerable increase in thickness were observed at or near 5,30 and 60 minutes. Following a mixed experimental design, plating proceeded at 49, 63 and 77 degree celcius for 5, 30 and 60 minutes, with bath agitation at 0 and 1000 rpm. Samples were observed for morphology and thickness measurement using the SEM and subjected to modified setup of the ASTM B 809, the Standard Test Method for Porosity in Metallic Coatings by Humid Sulfur Vapor.
Immersion-Sn deposit thickness was found to exhibit linear growth with square root of plating time, which is characteristic of a product layer diffusion (PLD)-controlled mass transfer system. The main effects of time and temperature were found to be the dominant factors affecting thickness of deposit, while interaction effects of time, temperature and agitation affected porosity of deposit.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Chemical kinetics; Tinning